Keragaan Jagung (Zea Mays l.) Bertongkol Ganda yang Ditanam Secara Tumpang Sari. (Performance of Prolific Type of Corn, Zea Mays L. In Intercropping). - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1986)
ABSTRAK Prolificacy in the maize entries growing in intercropping systems might contribute to both a yield advantage and the maximizing of productive land usage. A field experiment was conducted to compare the performance of prolific and non-prolific types of maize grow-. ing in association with dry beans and in association with spring wheat. Crosses of non-prolific x non-prolific, non-prolific x prolific, and prolific x prolific types were evaluated at four plant population levels. â¢ The results indicated that the prolific type was capable of producing higher yields than the non-prolific type at any given plant population and/or cropping system. The maize-bean intercropping produced higher yield in terms of total yields in combination, total food energy, and protein production. Selection for prolificacy combined with other desired traits in maize grown under the monocultural condition seems to be a promising and effective approach for favorable performance in intercropping systems. Key word: Tumpangsari, protein production, jagung